Description of six new species from Mesalina watsonana complex in the Iranian plateau and neighboring regions - Boroumand, Hamid; Bafti, Soheila Shafiei; Saberi-Pirooz, Reihaneh; Böhme, Wolfgang; Ahmadzadeh, Faraham (Zootaxa, 2024)
Mesalina watsonana is a species complex with a wide distribution range in Iran, some parts of Turkmenistan, Afghanistan, Pakistan, and northwest India. Recent molecular and morphological investigations detected remarkable hidden diversity among the geographical populations of the complex, more likely referring to the persistence of undescribed species. In this study, we conducted a very detailed sampling of localities and carried out a morphological study to investigate populations within the complex. Investigation of morphological features within the M. watsonana species complex indicated that it consists of seven distinct populations. They include the West-Southeast-South, East-Northeast, East Dasht-e Kavir, West Dasht-e Kavir, and two central groups (Halil and Kerman groups). Considering our findings, each of the seven populations corresponding to distinct geographic regions should be recognized as species. The six new species include Mesalina khuzestanensis sp. nov., Mesalina halilica sp. nov., Mesalina kermanensis sp. nov., Mesalina ardestanica sp. nov., Mesalina bardaskanensis sp. nov., Mesalina esfarayensis sp. nov. which are distinctive from each other due to their unique morphological characteristics.